AB0643 Th-17 Cytokines and Interstitial Lung Involvement in Systemic Sclerosis. (15th July 2016) - Nicola, S.; Fusaro, E.; Rolla, G.; Bucca, C.; Peroni, C.; Heffler, E.; Cassinis, M.; Ferraris, A.; Boita, M.; Parisi, S.; Brussino, L.
Abstract : Background: T Helper 17 (Th17) cytokines play an important pathogenetic role in most of autoimmune diseases, but their role in lung impairment in systemic sclerosis (SSc) is still poorly known. Objectives: We aim to evaluate whether Th17-related cytokines are detectable in serum and in exhaled breath condensate (EBC) of patients affected by SSc and whether their concentrations are related to clinical parameters of lung impairment in diffuse SSc. Methods: The outpatients with SSc according to ACR criteria attending Clinic of Rheumatic Disease, Città della Salute e della Scienza in Turin, between May 2014 and March 2015 were enrolled into the study, as well as a group of healthy non-smokers subjects, enrolled as controls. The study was approved by ethical committee and each patient released his informed consent; smokers, patients with asthma, COPD, history of cancer or other autoimmune diseases, current corticosteroids or immunosuppressive drugs therapy, recent (last 8 weeks) or current airway or systemic infection were excluded from the study. All patients underwent pulmonary function tests: spirometry, flow-volume curves, residual volume and diffusing capacity of the lung for carbon monoxide (DLCO), thoracic CT-scan analysed according to Global Warrick score and six minutes walking tests (6MWT). EBC and blood samples were collected in all the patients and controls. Serum and EBC Th-17 related cytokines (IL-17A, IL-21, IL-22, IL-23, IL-1β), TGF-β, TNF-α, IL-6 and IL-10 were measured using an xMAP technology and analysed by a multiplex immunoassay. Results: 29 outpatients affected by SSc were enrolled, as well as 20 healthy controls. 17 patients (1 male) were affected by limited SSc (lSSc) and 12 (no men) were affected by diffuse SSc (dSSc); the mean age was 64.5±15.5 yrs. All serum cytokines were significantly higher in patients than in controls (p<0.05), except for IL-1β (p=0.063) and TGF-β (p=0.900); all EBC cytokines were significantly higher in patients than controls (p<0.05). No difference in serum cytokines concentrations was observed between lSSc and dSSc, while all Th17-related cytokines in EBC were significantly higher in dSSc than in lSSc (p<0.05). In dSSc, serum IL-10 levels were significantly correlated with CT Global Warrick score (p=0.007, r=0.730), with DLCO (r=-0.664, p=0.018) and with 6MWT (r=-0.857, p=0.001). Serum TNF-α and IL-23 levels significantly correlated with the CT Global Warrick score (r=0.699, p=0.011 and r=0.659, p=0.020 respectively) and IL-23 also correlated with FVC (r=-0.578, p=0.049). In EBC, IL-1β significantly correlated with CT Global Warrick score (r =0.434, p=0.016) and with DLCO (r=-0.492, p=0.007), while IL-17 negatively correlated with DLCO (r=-0.394, p=0.042). Conclusions: In conclusion, our results show a correlation between Th-17 cytokines measured in serum and in EBC, with interstitial lung involvement of patients with diffuse SSc, underlining the importance of targeting these cytokines in the development of new therapeutic approaches against lung fibrosis. Disclosure of Interest: None declared